Performance Evaluation of CNTFETs Fabricated with Carbon Nanotubes of Different Synthesis Methods - Yahya, Iskandar; Hassan, Muhammad Azuddin; Mustaza, Seri Mastura; Abdullah, Huda; Clowes, Steven K.; Silva, S. Ravi P. (International Journal of Integrated Engineering, 2022)
Single walled carbon nanotubes (SWCNTs) exhibit extraordinary electronic properties that render it as an exciting candidate to be applied as the active channel of high-performance carbon nanotube field effect transistors (CNTFETs). The electronic properties of SWCNTs have been demonstrated to be dependent on the tube intrinsic properties that includes structural defects, chirality and diameter. Structural tube defects can be affected by the synthesis method and therefore the latter should also affect the device performance. Hence, this paper aims to present the influence of SWCNTs source synthesis method towards the resulting CNTFET device characteristics. A total of four SWCNT samples were sourced from different synthesis methods in fabricating CNTFETs. The synthesis methods are arc-discharge and three different variation of chemical vapor deposition (CVD) processes, which are DIPS, HiPco and CoMoCAT, respectively. Prior to fabrication, the SWCNT samples were characterized via Raman spectroscopy to quantify the tube defect levels of each sample, which are directly proportional to the G-peak to D-peak height ratio, G/D. Electrical characterization was carried out via 3-terminal field effect I-V measurement to evaluate key device performance parameters such as on-off current ratio, ION/IOFF, transconductance, gm, subthreshold slope, Sp and field effect mobility, ÂµFE. Analysis shows that G/D affects the IÂOFF more significantly relative to ION, resulting in increasing ION/IOFF, and hence switching performance, when G/D increases. It is shown an increase of 50% to the G/D of the SWCNT source resulted in 860% increase in ÂµFE. Based on the correlation between the optical analysis and electrical measurement, we conclude that the SWCNT growth method can significantly affect the CNTFET device performance.